A 6 MW/m2 High Heat Flux Testing Facility of Irradiated Materials Using Infrared Plasma-Arc Lamps. (3rd October 2019) - Sabau, Adrian S.; Tokunaga, Kazutoshi; Littleton, Michael G.; Kiggans, James O.; Schaich, Charles R.; Dinwiddie, Ralph B.; Moore, Daniel T.; Ueda, Yoshio; Katoh, Yutai
Abstract: Assessing the effect of neutron irradiation of plasma-facing materials has been challenging due to both the technical and radiological challenges involved. In an effort to address the radiological challenges, a facility was developed to conduct high heat flux testing (HHFT) of inherently small samples of neutron-irradiated materials. A new line-focus reflector was designed and fabricated at Oak Ridge National Laboratory for a plasma-arc lamp (PAL) to attain a source heat flux of 12 MW/m 2 . The new reflector was fabricated with two ports for monitoring specimen condition during HHFT. At the same operational conditions for PAL, the absorbed heat flux in tungsten was increased from 1.39 MW/m 2 with the uniform irradiance reflector to 5.12 MW/m 2 for the line-focus reflector. This fourfold increase in the heat flux, at the same PAL electrode lifetimes, enabled cost-effective facility operation for a high number of cyclic high heat flux tests. Specifically, the test section is confined to a hemispherical dome, and specimens are bolted directly to a water-cooled copper alloy rod. Temperature measurement in the PAL facility was a main challenge due to a limited line of sight. For the first time in a PAL facility operating at high heat fluxes, the specimen surface temperature was directly measured during HHFT with a pyrometer. The HHFT data, which were obtained in this upgraded PAL facility, demonstrated the facility readiness for irradiated materials.